Efficacy and safety of endoscopic retrograde cholangiopancreatography in pregnancy: A high-volume study with long-term follow-up - Konduk, Buğra Tolga; Bayraktar, Onur (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Pancreaticobiliary diseases are observed more frequently in pregnancy due to increased biliary stone formation. There are some concerns about the use of endoscopic retrograde cholangiopancreatography (ERCP) because of potential fetal exposure to radiation and serious adverse events, such as post-ERCP pancreatitis, which increases fetal or maternal morbidity and mortality. The aim of this study was to evaluate the efficacy and safety of ERCP during pregnancy and to present our experience.Materials and Methods: This study included 25 pregnant patients who underwent ERCP due to biliopancreatic pathologies between 2010 and 2017. Indications for ERCP were choledocholithiasis (n=12), biliary pancreatitis (n=9), and acute cholangitis (n=4). ERCP procedures were performed using fluoroscopy (n=18) and the non-radiation technique (n=7). The duration of fluoroscopy was recorded in all cases. Fetal and maternal complications were both assessed. Results: The mean age of patients was 29.4 (range, 21–40) years, and the mean duration of pregnancy was 19.9 weeks. All the 25 ERCP procedures were performed successfully. Biliary sphincterotomy was performed in all patients, and 18 patients with choledocholithiasis underwent stone extraction. The average procedure duration was 11 min, and the average duration of fluoroscopy was 6 s. There were no major complications in any patient. After the deliveries, the newborns were apparently healthy during the follow-up period of 1–7 years.Conclusion: Either conventional or non-radiation ERCP procedures can be performed successfully in pregnancy, with no increase in the number of feto-maternal complications when performed by experienced endoscopists.